STRATEGI GURU PAK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI KOMUNIKASI - Erikson Simbolon; Ginting Munthe, Fico Rasmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies of Catholic Religious Education teachers in improving students’ critical thinking skills through communication at SMP Swasta RK Fransiskus Xaverius Namorambe Deli Serdang Sumatera Utara. This research employed a descriptive qualitative approach. The research participants consisted of the principal, Catholic Religious Education teacher, and Grade VIII students. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that students’ critical thinking skills were reflected in their ability to ask questions, express opinions and arguments, analyze problems, evaluate information, draw conclusions, and communicate critically. The study also found that teachers improved students’ critical thinking skills through learning planning, preparation of contextual learning materials, application of active learning methods, utilization of learning media, and continuous learning evaluation. These strategies created active, participatory, and meaningful learning experiences that supported the development of students’ critical thinking skills in Catholic Religious Education learning.